Пошаговое объяснение:
а)(17-5) × у = 60
12у=60
у=60:12=5
(17-5) × 5 = 60
60=60
с) z : (100-15) = 2
z = (100-15) *2
z = 85*2= 170
170 : (100-15) = 2
2=2
b) (х+24) : 6 = 30
(х+24) = 6 *30
х= 180-24 = 156
(156+24) : 6 = 30
30=30
d) 92 -6 • u = 8
-6 • u = 8 - 92= -84
u = 84/6 = 14
92 -6 • 14 = 8
8=8
Пошаговое объяснение:
а)(17-5) × у = 60
12у=60
у=60:12=5
(17-5) × 5 = 60
60=60
с) z : (100-15) = 2
z = (100-15) *2
z = 85*2= 170
170 : (100-15) = 2
2=2
b) (х+24) : 6 = 30
(х+24) = 6 *30
х= 180-24 = 156
(156+24) : 6 = 30
30=30
d) 92 -6 • u = 8
-6 • u = 8 - 92= -84
u = 84/6 = 14
92 -6 • 14 = 8
8=8